Defining the characteristics of physically demanding winch rescue in helicopter search and rescue operations. (May 2021) - Meadley, Ben; Bowles, Kelly-Ann; Smith, Karen; Perraton, Luke; Caldwell, Joanne
Abstract: Helicopter emergency medical service search and rescue (HEMS SAR) paramedics perform physically demanding winch rescues. Rescue organisations require valid physical employment standards (PES) to ensure personnel can adequately perform duties. There are no studies describing validated PES for HEMS SAR. We convened a subject matter expert (SME) focus group to review historical case data and generate task descriptions for land and water winch rescue as the basis for development of task simulations to assess physiological workload. Sixteen helicopter rescue paramedics with a mean age of 47 (range, 36–52) years and 8 (2–20) years' experience in helicopter rescue participated in a SME focus group. When provided with data from historical cases, SMEs achieved consensus (≥80%) when generating descriptions of winch rescue. This method may be useful to develop simulations for assessment of physiological demands of winch rescue and similar tasks, and to enhance validity and reliability of PES for rescue organisations. Highlights: Helicopter search and rescue teams undertake high-risk winch rescues. Valid physical employment standards for this group are needed. Subject matter experts in focus groups can reliably be used to define tasks. The use of detailed data from operational rescues aids accurate task definition. Accurate task definition may aid development of reliable physical standards.